Novel process chain for forming micro gears with a module of 0.1 mm – Potentials and approaches for extending process limits - Leicht, Miriam; Merklein, Marion (Journal of Manufacturing Processes, 2025)
Micro gears are considered essential components of micro drive systems, which offer great potential for medical technology, measurement technology and robotics due to their small dimensions and their precise and highly dynamic transmission of movements and forces. However, established manufacturing processes such as hobbing, lithography technology or micro powder injection moulding are too time-consuming and cost-intensive for mass production. Therefore, new technological approaches are required. A multi-stage process chain of micro bulk forming from sheet metal offers great potential for the mass production of high-performance micro gears. In the first stage, a pin is extruded from sheet metal. Afterwards, the pin is geared by lateral extrusion, which is subsequently separated from sheet by shear cutting. The objective of this research work is to gain a fundamental understanding of the potentials and limitations of a multi-stage process chain for the production of micro gears with a module of m = 0.1 mm. The obtained knowledge serves as foundation for the development and analysis of approaches to overcome existing process limitations in terms of material efficiency and tool stress. The experimental results reveal, that a local adjustment of the material properties in the forming zone as well as a tool-sided limitation of the material flow radially outwards are suitable for improving the material efficiency.
CRIS-Team Scopus Importer:2025-04-25
Keywords: Cold forming; Micro forming; Micro gear; Size-effect